ANALISIS KEKERASAN VERBAL DALAM VIDEO YOUTUBE TIMUR KOTA AMBONAI “ PT. LOLANG PENNI”(KAJIAN SEMIOTIKA) - Anugrah, Aldan; Muh. Safar; Muhammad Idris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms of verbal violence and the meanings of harsh words found in the YouTube video Ambo Nai